2001
DOI: 10.1016/s0022-5347(05)66578-0
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Age as a Risk Factor for Hypospadias

Abstract: Hypospadias is significantly associated with increasing maternal age. Women who elect to delay childbearing until their mid 30s or later should be aware that their offspring are at increased risk of hypospadias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
26
0
10

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(41 citation statements)
references
References 20 publications
5
26
0
10
Order By: Relevance
“…Taken together, it is becoming increasingly clear that advanced maternal age is associated to hypospadias. Our finding is also consistent with previous studies showing that the risk is higher for having a child with hypospadias Type II or III than for Type I [9, 2021]. But the exact nature of this association still needs to be determined; is it related to genetic defects associated to aging, to subfertility, or any other factor?…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Taken together, it is becoming increasingly clear that advanced maternal age is associated to hypospadias. Our finding is also consistent with previous studies showing that the risk is higher for having a child with hypospadias Type II or III than for Type I [9, 2021]. But the exact nature of this association still needs to be determined; is it related to genetic defects associated to aging, to subfertility, or any other factor?…”
Section: Discussionsupporting
confidence: 92%
“…A case-control population study in Sweden for the time period 1983–1993 found that the odds ratio (OR) of having a child with hypospadias among mothers > 40 years of age was 1.30 with a 95% confidence interval (CI) between 0.67-2.53 [8]. In the USA, it has been reported that OR for mothers > 35 years of age in the state of California was 1.2 (95% CI: 1.1-1.4) for the time period 1983–89, whereas the odds of having a child with severe hypospadias for years 1990–95 in that state was 1.5 (95% CI: 1.2-1.7) [9]. The same study established that the OR for the state of New York was 1.2 (95% CI: 1.1-1.3) for years 1983–96 [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These anomalies may be caused by placental insufficiency, which may result from many factors, including maternal age, parity, and multiple births 12. Advanced maternal age was found to be associated with an increased incidence of structural birth defects, including urethral abnormalities 13. Similarly, we observed significant relationships between hypospadias and maternal age extremes.…”
Section: Discussionsupporting
confidence: 58%
“…In rural areas where only a smaller population is considered, variations within the population cohort may be problematic, leading to an apparently reduced association with deprivation. Fisch et al 9 have recently reported that the risk of genital anomaly increases with increasing maternal age. Our data suggest that this risk may be independent of socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%